“Mr Hitler,” Greta Garbo and the Jew Hidden in the Grass. The Literary Representation of the Holocaust in Ruth Tannenbaum by Miljenko Jergović - Szperlik, Ewa (Poznańskie Studia Slawistyczne, 2023)
This article is an attempt to provide an insight into the fate of the Jewish diaspora in Zagreb, a city marked by the spectre of the Second World War. The events in the diegetic world are based on the fictionalised, tragic life of a young Jewish actress Lea Deutsch (1927-1943), who was acclaimed a prodigy of the Zagreb theatre scene and was killed in Auschwitz. Miljenko Jergović undertook the difficult task of addressing Croatian antisemitism, the circumstances surrounding the creation of the Independent State of Croatia (1941-1945), of which the darkest outcome was the Jasenovac concentration camp. The analysis of the work is part of a wide-ranging discussion on the acceptable ways to depict the Holocaust (language and form). The Croatian writer's novel highlights the topos of the eternally wandering Jew; he also dispels the myth about small promised lands in the history of Jews, who were scattered across Europe and had to face local exclusion, antisemitism and ghettoisation.